1977
DOI: 10.1111/j.1745-4565.1977.tb00259.x
|View full text |Cite
|
Sign up to set email alerts
|

Botulogenic Properties of Vegetables With Special Reference to the Molecular Size of the Toxin in Them

Abstract: The molecular sizes of Clostridium botulinum type A, B, E, and F toxins produced in string beans, mushrooms, tuna fish and pork were determined to provide an explanation for the high botulogenic properties of vegetables. Type A and B organisms produced the orally more toxic 16S and 19S molecular‐sized toxins in vegetables, whereas they produced the orally less toxic 12S and only rarely some 16S toxin in tuna fish and pork. Type E and F organisms produced only 12S toxin in any food or culture medium, but additi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
5
0

Year Published

1980
1980
2012
2012

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(8 citation statements)
references
References 23 publications
3
5
0
Order By: Relevance
“…botulinum failed to grow on fresh celery (Johnson 1979). This work confirmed the ability of potato (Notermans et al 1981;Lund et al 1988;Dodds 1989), mushroom, green beans (Sugii and Sakaguchi 1977;Montville and Conway 1982), carrot (Montville and Conway 1982;Notermans 1993) and sweet corn (Montville and Conway 1982) to support growth and toxin production by proteolytic Cl. botulinum.…”
Section: Resultssupporting
confidence: 70%
“…botulinum failed to grow on fresh celery (Johnson 1979). This work confirmed the ability of potato (Notermans et al 1981;Lund et al 1988;Dodds 1989), mushroom, green beans (Sugii and Sakaguchi 1977;Montville and Conway 1982), carrot (Montville and Conway 1982;Notermans 1993) and sweet corn (Montville and Conway 1982) to support growth and toxin production by proteolytic Cl. botulinum.…”
Section: Resultssupporting
confidence: 70%
“…Previous studies have shown that, among type A, B, C, and D toxins of different molecular sizes, type B-L toxin produced by strain Okra is the most potent in oral toxicity to mice (11,12). The toxin is produced not only in laboratory media but also in foodstuffs (17). Moreover, the present study demonstrated that B-L toxin is produced by all strains of C. botulinum type B examined.…”
supporting
confidence: 59%
“…At least in foods, neurotoxin is not found in the uncomplexed state. Since M complexes in a type A culture fluid become L complexes during dialysis against a phosphate buffer, the degree of complexing also depends on the solvent (198).…”
Section: Structure Of Complexesmentioning
confidence: 99%
“…Since these complexes form in mixtures made with pure neurotoxin and the complementary nontoxic protein, the constituents could be independently synthesized and then aggregate. On the other hand, if neurotoxic protein is never by itself in culture fluids (80,198) but always in M complexes (or the M part of larger complexes), the two components are at least synthesized concomitantly. The demonstration of a toxic entity of M-complex dimensions which could not be dissociated into two equal parts without breaking a covalent bond would be evidence that the M complex is the product of a single gene.…”
Section: Nomenclaturementioning
confidence: 99%